Polidextrose enhances calcium absorption and bone mineralization in ovariectomized rats - Weisstaub, Adriana (2013)
Purpose. To evaluate the effect of polydextrose (PDX) on Ca bioavailability and prevention of loss of bone mass. Methods. Twenty-four two-month-old ovariectomized rats were fed three isocaloric diets only varied in fiber source and content up to 60 days (FOS group, a commercial mixture of short- and long-chain fructooligosaccharide, OVX group fed AIN 93 diet, and PDX group). A SHAM group was included as control. Apparent Ca absorption percentage (%ABS), changes in total skeleton bone mineral content (tsBMC) and bone mineral density (BMD) and femur BMD, % Bone Volume, Ca and organic femur content, caecal weight, and pH were evaluated. Results. %ABS and caecum weight of PDX and FOS were higher, and caecum pH was lower compared to OVX and SHAM. PDX reached a higher pH and lower caecum weight than FOS possibly because PDX is not completely fermented in the colon. Changes in tsBMC and femur BMD in FOS and PDX were significant lower than SHAM but significantly higher than OVX. % Bone Volume and femur % of Ca in PDX were significantly higher than OVX and FOS but lower than SHAM. Conclusions. PDX increased Ca absorption and prevented bone loss in OVX rats.